2015
DOI: 10.1589/jpts.27.1353
|View full text |Cite
|
Sign up to set email alerts
|

The effects of task-oriented versus repetitive bilateral arm training on upper limb function and activities of daily living in stroke patients

Abstract: Abstract.[Purpose] The purpose of this study was to investigate the effects of task-oriented bilateral arm training and repetitive bilateral arm training on upper limb function and activities of daily living in stroke patients. [Subjects] Forty patients with hemiplegia resulting from stroke were divided into a task orientied bilateral arm training group (n=20) and a repetitive bilateral arm training group (n=20). [Methods] The task-oriented group underwent bilateral arm training with 5 functional tasks, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 16 publications
0
13
0
3
Order By: Relevance
“…However, a review of 18 clinical trials of simultaneous bilateral training found no statistically significant results for performance of Acclivities of Daily Living (ADL) functional movement of the arm or hand (Coupar et al, ). In contrast, TO training showed greater improvement in upper limb function and activities of daily living, when compared with bilateral training (Song, ). Modified CIMT and modified bilateral arm training showed no superior effect on upper limb motor function post‐stroke as compared with dose‐matched conventional intervention (van Delden et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a review of 18 clinical trials of simultaneous bilateral training found no statistically significant results for performance of Acclivities of Daily Living (ADL) functional movement of the arm or hand (Coupar et al, ). In contrast, TO training showed greater improvement in upper limb function and activities of daily living, when compared with bilateral training (Song, ). Modified CIMT and modified bilateral arm training showed no superior effect on upper limb motor function post‐stroke as compared with dose‐matched conventional intervention (van Delden et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bu çalışmalarda iş uğraşı tedavilerine ek olarak yapılan bilateral eğitimin GYA gerçekleştirme becerisini anlamlı olarak artırdığı bildirilmiştir. 36,37 İnmeli hastalarda üst ekstremitede en sık karşılaşılan kasiskelet sistem komplikasyonu ağrıdır. Plejik taraftaki ağrı rehabilitasyon sürecini de olumsuz etkilemektedir.…”
Section: Tedaviunclassified
“…Conventional rehabilitation for hand function and neuroplasticity, such as constraint-induced movement therapy [7], high-intensity training, and repetitive task-oriented training [8], often have unsatisfactory results due to insufficient patient motivation. However, previous evidence suggests that intensive repeated training is likely necessary to modify neural organization and promote recovery of hand motor skills in stroke patients [9,10]. To overcome these limitations, game-based virtual reality (VR) training is becoming a promising technology to promote motor recovery by providing high-intensity and repeated task-oriented rehabilitation with 3-dimensional game programs involving patient body movement [11][12][13].…”
Section: Introductionmentioning
confidence: 99%